Interaction of Several Calcon Compounds of Paracetamol Based Toward the Role of Enzyme Protein in Antibacterial Mechanism - Anasda Amal Fathullah; Wisnu Cahyo Prabowo; Rolan Rusli (Department of Chemistry, Faculty of Sciences and Informatics, Jenderal Achmad Yani University, 2018)
Kalkon is a secondary metabolite of the flavonoid group that is found in nature, especially in plants. Kalkon has various activities such as cytotoxic, antiviral, anesthetic, antimicrobial, antiinflammatory, and so forth. The aim of this research is to know the antibacterial activity of kacco-based derived paracetamol compound by using docking method against bacterial protein Escherichia coli and Bacillus subtilis. The results showed that the compound 3- (4-Metoxyphenyl) -N- (4-Chlorophenyl) Acrylamide, 3- (4-Hydroxyphenyl) -N- (4-Chlorophenyl) Acrylamide, and 3- (4-Hydroxy-3-Methoxyphenyl ) -N- (4-Chlorophenyl) Acrylamide showed good activity with an average rmsd-refine score <2. The kalkon derivative binds complex with amino acid bacteria such as Ile 173, Asn 267, Lys A449, Thr 265, and Arg A389.